2006
DOI: 10.1097/01.mop.0000193297.40388.19
|View full text |Cite
|
Sign up to set email alerts
|

Airway clearance in children with neuromuscular weakness

Abstract: Secretion extraction and mobilization techniques are safe, even in infants who require airway clearance assistance. To date, however, criteria specific for children are lacking to determine when such modalities should be used and which ones are most effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 35 publications
0
42
0
Order By: Relevance
“…Significant behavioral differences corroborated by a P value = 0.02. It is worth mentioning here that a higher peak expiratory flow may be associated with better ability to cough by part of the patients, which is relevant in order to avoid accumulation of secretions in the airways of the patients [12,17].…”
Section: Resultsmentioning
confidence: 99%
“…Significant behavioral differences corroborated by a P value = 0.02. It is worth mentioning here that a higher peak expiratory flow may be associated with better ability to cough by part of the patients, which is relevant in order to avoid accumulation of secretions in the airways of the patients [12,17].…”
Section: Resultsmentioning
confidence: 99%
“…Peak cough flows of 160 to 270 L/min have been described as acceptable levels to clear the airway; below this point, patients are more susceptible to infection and respiratory failure. 43,44 A mask interface allows children and adults with facial weakness to achieve a reliable value for both peak cough flow and vital capacity. Simply asking a child to cough can also be used to assess cough effectiveness.…”
Section: Consensus Care Guidelines For Congenital Muscular Dystrophiesmentioning
confidence: 99%
“…Chest insufflation increases the volume of air in the chest to achieve a more effective cough flow. 43,44 Chest insufflation can be done by breath stacking with glossopharyngeal breathing (frog breathing), an Ambu bag, intermittent positive-pressure breathing, mechanical in/exsufflation (e.g. Cough Assist™), and noninvasive positive-pressure ventilation.…”
Section: Consensus Care Guidelines For Congenital Muscular Dystrophiesmentioning
confidence: 99%
“…95 Assisted cough with a sustained inflation provided by a manual resuscitator bag, followed by tussive squeeze, is effective but requires skilled trained staff (Table 3). [96][97][98][99][100][101][102] Mechanical insufflation-exsufflation (eg, with CoughAssist, Philips Respironics, Murrysville, Pennsylvania) benefits airway clearance by providing inspiratory pressure (which gets air distal to the mucus) then fast expiratory flow, which simulates cough. 103 Streigl et al found that, with an infant lung model with a tracheostomy tube during mechanical insufflation-exsufflation, an insufflation time of Ն 1 second is required to achieve equilibration of alveolar pressure to insufflation pressure.…”
Section: Neuromuscular Diseasementioning
confidence: 99%